Pervaporation of Acetic Acid-Water Mixture Using Silica Membrane Prepared by Sol-Gel Method - Samuel P. Kusumocahyo; Masao Sudoh (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Silica membranes were developed and tested for the separation of acetic acid and water by pervaporation. Thin microporous silica membranes were prepared on a porous alumina tube by sol-gel method using tetraethyl orthosilicate (TEOS) as the silica precursor. Colloidal and polymeric silica sols were prepared by hydrolysis of TEOS. The pervaporation experiment results revealed that the silica membranes showed water selectivity towards acetic acid. The permeate flux and the separation factor were strongly influenced by the composition of the silica sols. For a feed concentration of 90 wt% acetic acid, the permeate flux varied between 0.016 to 0.91 kg/m2 h, with the separation factor varying between 3.7 and 324.